Availability and Utilization of Printed Educational Resources for Teacher Job Performance in Rural and Urban Technical Colleges in Anambra State, Nigeria - Udochukwu Chukwunwike Asuzu (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The availability and utilization of printed educational resources play a vital role in enhancing teacher performance in technical colleges that emphasize practical skills; however, significant disparities in access persist between rural and urban institutions. Objective: This study aims to investigate the availability and utilization of printed educational materials by teachers in rural and urban technical colleges in Anambra State. Method: A descriptive survey research design was employed. The population consisted of 647 teachers from 15 technical colleges in Anambra State, from which a random sample of 343 teachers was selected. Data were collected using a validated questionnaire and analyzed using Chi-Square and z-tests. Result: The findings revealed that only 25.40% of printed educational resources were available in rural technical colleges, compared to 38.78% in urban colleges. Utilization rates were higher for certain resources, such as registers and workbooks, but lower for others, including dictionaries. Statistically significant differences were found between rural and urban colleges in both availability and utilization of resources. Conclusion: The study highlights substantial disparities in the availability and utilization of printed educational resources between rural and urban technical colleges. These disparities indicate the need for targeted interventions, particularly in rural areas, to enhance educational resource provision. Contribution: This study contributes to the existing literature by providing empirical evidence on resource inequality in technical education and offers insights to policymakers and educational stakeholders for promoting equitable distribution and effective utilization of printed educational resources.